2011
DOI: 10.1038/ajg.2011.129
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Harms of Nasal Calcitonin in Improving Bone Density in Young Patients With Inflammatory Bowel Disease: A Randomized, Placebo-Controlled, Double-Blind Trial

Abstract: Background & Aims There are very few published studies of agents having the potential to improve bone health in children with inflammatory bowel disease (IBD). Our aim was to establish the efficacy and safety of intranasal calcitonin in improving bone mineral density (BMD) in young patients with IBD and to define additional factors that impact bone mineral accrual. Methods We conducted a randomized, placebo-controlled, double-blind clinical trial in sixty-three participants, ages 8 to 21 yrs, with a spinal B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 51 publications
(77 reference statements)
1
7
0
Order By: Relevance
“…Although most of the patients had inactive disease, their bone health was still impaired. The results on lower aBMD in pediatric IBD patients are in concordance with previous studies demonstrating persistently impaired BMD after diagnosis of the disease [6,14,31,32]. One-third of the patients had delayed BA, and BA-adjusted aBMD Z scores were significantly higher than CA-adjusted values, which emphasizes the importance of correcting the BMD values for delayed pubertal maturation when analyzing DXA results in both CD and UC patients.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although most of the patients had inactive disease, their bone health was still impaired. The results on lower aBMD in pediatric IBD patients are in concordance with previous studies demonstrating persistently impaired BMD after diagnosis of the disease [6,14,31,32]. One-third of the patients had delayed BA, and BA-adjusted aBMD Z scores were significantly higher than CA-adjusted values, which emphasizes the importance of correcting the BMD values for delayed pubertal maturation when analyzing DXA results in both CD and UC patients.…”
Section: Discussionsupporting
confidence: 90%
“…One-third of the patients had delayed BA, and BA-adjusted aBMD Z scores were significantly higher than CA-adjusted values, which emphasizes the importance of correcting the BMD values for delayed pubertal maturation when analyzing DXA results in both CD and UC patients. Most previous studies that have evaluated BA of pediatric IBD patients have reported significant delay of BA, with a mean difference of 0.5-1.2 years to CA [6,16,17,[32][33][34]. Two studies on IBD patients found no difference between BA and CA [3,5].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The studies enrolled in this meta-analysis showed that bisphosphonates can also reduce the risk of fractures in IBD patients. Only one clinical trial thus far showed that intranasal calcitonin is not able to increase BMD in young IBD patients [ 34 ]. Two prospective studies revealed the beneficial effect of infliximab on bone metabolism both in CD and in UC patients [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three patients received calcitonin at the time of the study; the effect of calcitonin on BMD was also considered insignificant 28 and these patients' DEXA values were included in further analyses. Two patients had discontinued bisphosphonate therapy 7-10 months (mean 8.5 mo) before the study; 3 patients were still receiving intravenous pamidronate and 1 patient once-weekly alendronate.…”
Section: Rheumatologymentioning
confidence: 99%